ANALISIS KARAKTER DALAM NOVEL BREAKING DAWN OLEH STEPHENIE MEYER - MARAMIS, FERNANDO (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2015)
ABSTRACTS Â â€œAnalisis Karakter Dalam Novel Breaking Dawnâ€ is a skripsi which is to fulfill one of the requirements to achieve the title of Sarjana Sastra. There are two main problems to be analyzed; those are â€œhow the characters are revealed in Breaking Dawn and â€œhow the method of characterization is applied in the novel. The purpose of this research are to identify human characters, to analyze and describe the characterization. In identifying characters, the writer used Robertsâ€™ theory about characters, in analyzing and describing the characterization, the writer used Perrineâ€™s theory about direct presentation and indirect presentation. For analyzing the data the writer used descriptive method and intrinsic approach. Â The results of this research show that there are several human characters found in the novel such as introvert, willing to sacrifice, calm, understanding, clever, wise, determinated, etc. The method of characterization found in this novel can be devided in two types: direct presentation and indirect presentation; these two types of presentation can be found in six characters in the novel, they are:Â Isabella (Bella) Swan, Edward Cullen, Jacob Black, Charlie Swan, Jasper Hale and Garret. Â Â Keywords: Characters, Method of characterization, Novel, â€œThe Breaking Dawnâ€.